The Effects of Reverse Logistics on Cost Control Abilities: An Insight into Manufacturing Companies in Malaysia - Fernando, Yudi; Sharon, Shih Sim Tan; Wahyuni-TD, Ika Sari; Tundys, Blanka (Inderscience Enterprises Ltd., 2017)
This study aims to examine the effect of reverse logistics on the ability of manufacturing firms to control costs. The data were collected from manufacturing firms registered under the Federation of Malaysia Manufacturers (FMM). A total of 275 manufacturing firms participated in this survey. The variance-based structural equation modelling (SEM) with the partial least square (PLS) was used to validate the measurement constructs and test the proposed hypotheses. The statistical results indicated that three dimensions constructs of reverse logistics: (1) remanufacturing; (2) material recycling; (3) green disposal have a significant and positive relation with the ability of firms to control costs. The firms need to practice green operations and sustainability orientation activities to maintain lower costs, improve the quality of products, stakeholders' well-being and lower carbon footprint for greener environments.